The effectiveness of a structured nursing intervention program on maternal stress and ability among mothers of premature infants in a neonatal intensive care unit - Ong, Swee Leong; Abdullah, Khatijah Lim; Danaee, Mahmoud; Soh, Kim Lam; Soh, Kim Geok; Lee, Daphne Siew Kee; Hussin, Emni Omar Daw (Wiley, 2019)
Aims and objectives: To investigate the effectiveness of a structured nursing intervention program on maternal stress and NICU-related maternal ability after the admission of premature infants to a neonatal intensive care unit (NICU). Background: Mothers of premature infants may face stress having premature infants, and their infants may be admitted to the NICU for a few weeks or months. The mothers’ experience of stress would be worse if they have low knowledge and poor NICU-related maternal ability. Mothers of infants admitted to the NICU require well-planned interventions to cope with psychological matters arising after an infant hospitalisation. Design: Quasi-experimental design. Methods: A total of 216 mothers were consecutively assigned to control and intervention groups. Each group consisted of 108 mothers. The mothers in both groups received questionnaire concerning maternal stress and NICU-related ability during their first visit to NICU (within 48 hr of admission). A structured nursing intervention was implemented for 10 days on mothers in the intervention group. The control group continued to receive existing practice nursing care. Mothers of both groups were again given the questionnaire on maternal stress and NICU-related ability after 14 days of admission. Results: In the intervention group, the difference between the mean total score of maternal stress and parental role and relationship subscale decreased significantly, compared to the control group (p = 0.04; p = 0.01) respectively. Maternal ability improved significantly in mothers in the intervention group 2 weeks postintervention, p < 0.001. Conclusion: A structured nursing intervention for mothers could significantly reduce maternal stress and promote maternal NICU-related abilities. Relevance to clinical practice: The results of the study could help neonatal nurses to develop an appropriate nursing intervention for parents with premature infants in the NICU. © 2018 John Wiley & Sons Ltd